2021
DOI: 10.1017/s0007114521001203
|View full text |Cite
|
Sign up to set email alerts
|

Maternal supplementation with Bacillus altitudinis spores improves porcine offspring growth performance and carcass weight

Abstract: The objective of this study was to evaluate the effect of feeding Bacillus altitudinis spores to sows and/or offspring on growth and health indicators. On day (D) 100 of gestation, 24 sows were selected and grouped as: control (CON), fed with a standard diet; and probiotic (PRO), fed the standard diet supplemented with B. altitudinis WIT588 spores from D100 of gestation until weaning. Offspring (n=144) from each of the two sow treatments were assigned to either a CON (no probiotic) or PRO (B. altitudinis-suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 43 publications
11
31
0
Order By: Relevance
“…Moreover, its ability of Zn biosorption has been mentioned in the field of remediation purposes ( 130 ). Crespo-Piazuelo et al found that supplementation of B. altitudinis spores improves porcine offspring growth performance ( 131 ). The most likely explanation is the stimulation of the immune system; however, the mechanism is not fully understood yet ( 93 , 131 ).…”
Section: Weaning Of Piglets and Diarrhea Occurrencementioning
confidence: 99%
“…Moreover, its ability of Zn biosorption has been mentioned in the field of remediation purposes ( 130 ). Crespo-Piazuelo et al found that supplementation of B. altitudinis spores improves porcine offspring growth performance ( 131 ). The most likely explanation is the stimulation of the immune system; however, the mechanism is not fully understood yet ( 93 , 131 ).…”
Section: Weaning Of Piglets and Diarrhea Occurrencementioning
confidence: 99%
“…The use of probiotics has emerged as a promising strategy to improve the reproductive performance of sows by increasing feed consumption along with lactation, reducing fat mobilization, promoting milk production, and increasing litter weight ( Alexopoulos et al, 2004 ; Böhmer et al, 2006 ; Kritas et al, 2015 ; Hayakawa et al, 2016 ; Zhang et al, 2020 ). Moreover, several studies have also shown that when probiotics are administered to sows, positive effects can be also seen in the performance of piglets, with increases in rates of growth ( Kritas et al, 2015 ; Betancur et al, 2021 ; Crespo-Piazuelo et al, 2021 ) and reduction in the clinical signs of post-weaning diarrhea ( Alexopoulos et al, 2004 ; Taras et al, 2005 ; Taras et al, 2006 ; Betancur et al, 2021 ). Although the mechanisms of action have not yet been fully elucidated, these benefits could have been derived from a beneficial modulation of the intestinal microbiota of nursing piglets by their mothers.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by our group, using this approach, transmission of the B. altitudinis strain to piglets born to sows fed probiotic spores was demonstrated. These animals had improved PW feed efficiency and residual growth performance 32 , proving the effectiveness of this delivery route. Another likely reason for the benefits observed from maternal supplementation is the early-life probiotic exposure.…”
Section: Discussionmentioning
confidence: 76%
“…A potentially beneficial effect of probiotic administration was the increase in butyrate-producing genera, such as Agathobacter, Faecalibacterium and Roseburia 73 , 74 . In another study by our group 32 , butyrate-producing taxa (e.g. Lachnospiraceae , Blautia , Ruminococcus and Roseburia ) were more abundant in the faeces and ileal digesta of the offspring from B. altitudinis- supplemented sows compared with those from unsupplemented sows.…”
Section: Discussionmentioning
confidence: 76%